Chemical properties and antioxidant activity of eight tomato hybrid fruits cultivated in Syria (Damascus University Journal of agriculture sciences, 2023)
This research was carried out in the laboratories of the General Commission for Scientific Agricultural Research in 2021. On order to determine some chemical properties and antioxidant activity of the fruits of  eight tomato hybrids (Shourouk, Ballade, Elegro, Pharah, FDR, Lamantin, Marah and Bravia) cultivated in Syria. The percentage of the dry matter ranged from 3.4% to 5.3%, and the total soluble solids from 2.2% to 5.2%, although the total titratable acidity ranged from 0.18% to 0.55%, and the percentage of total the soluble solids to the total acidity ranged between 5.64 and 18.33. The hybrid “Lamantin” was significantly superior to the rest of the hybrids in terms of its content of ascorbic acid with an average of 11.44 mg/100 g, whereas for phenols, “Bravia” had the highest phenol content of 16.35 mg/100g, while the hybrid “Marah” was superior for its lycopene content of 89.31 mg/kg and the antioxidant activity by DPPH method of 89.10%. A strong positive correlation was observed between ascorbic acid and antioxidant activity (r=0.79).
Keywords: Tomato hybrids; ascorbic acid; total phenolic compounds; antioxidant activity; lycopene content